2022
DOI: 10.1055/a-1768-4371
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting D-dimer to Lung Disease Extent to Exclude Pulmonary Embolism in COVID-19 Patients (Co-LEAD)

Abstract: Introduction: D-dimer measurement is a safe tool to exclude pulmonary embolism (PE) but its specificity decreases in COVID-19. Our aim was to derive a new algorithm with specific D-dimer threshold in COVID-19 patients. Methods: We conducted a French multicenter, retrospective cohort study among 774 COVID-19 patients with suspected PE. D-dimer threshold adjusted to computed tomography (CT) extent of lung damage was derived in a patient set (n=337), and its safety assessed in an independent validation set (n=337… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In the recently published Co-LEAD study, authors stratified D-dimer levels by the extent of parenchymal lung involvement, concluding two different D-dimer thresholds for continuing to CTPA [ 13 ]. In this study, we sought a similar approach and found that a dichotomous threshold, depending on lung tissue involvement (D-dimer/age > 20 for non-severe lesions, D-dimer/age > 70 for severe lesions), may be diagnostically useful.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently published Co-LEAD study, authors stratified D-dimer levels by the extent of parenchymal lung involvement, concluding two different D-dimer thresholds for continuing to CTPA [ 13 ]. In this study, we sought a similar approach and found that a dichotomous threshold, depending on lung tissue involvement (D-dimer/age > 20 for non-severe lesions, D-dimer/age > 70 for severe lesions), may be diagnostically useful.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several studies advocate the use of higher Ddimer thresholds (between 2500 and 2900 µg/L), or adjusted to computed tomography extent of lung damage, despite a lower sensitivity. 21 Conversely, a recent study used the YEARS algorithm with no D-dimer threshold adjustment, and PE was confirmed in 13% of patients who underwent CTPA. 22 Currently, the ISTH committee recommends standard-of-care objective testing in case of clinical suspicion of VTE (CTPA, ventilation/perfusion scan, magnetic resonance imaging, venography, Doppler ultrasonography).…”
Section: -D Imer Te S Ting In Patients With Cov I D -19mentioning
confidence: 99%
“…Cutoff values for VTE exclusion need to be defined in patients with COVID‐19 20 . Several studies advocate the use of higher D‐dimer thresholds (between 2500 and 2900 µg/L), or adjusted to computed tomography extent of lung damage, despite a lower sensitivity 21 . Conversely, a recent study used the YEARS algorithm with no D‐dimer threshold adjustment, and PE was confirmed in 13% of patients who underwent CTPA 22 .…”
Section: D‐dimer Testing In Patients With Covid‐19mentioning
confidence: 99%
“…COVID-19 susceptibility, severity, and disease outcome reflect an association with gene expression patterns, mutations, deletions, and polymorphisms [8,9]. Some genetic polymorphisms in host ACE1, APOE, and IFITM3 genes demonstrate an increased infection risk, while polymorphisms in ACE2, AGTR1, TMPRSS2, VDR, and TNFA are associated with the severity of disease [10][11][12][13][14][15][16][17]. Studies have also indicated a high infectivity potential and increased severity of COVID-19 in the A blood group serotype, while the O blood group serotype is observed to be protective against infection [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, D-dimer holds promise as a prognostic biomarker, alongside procalcitonin, Creactive protein, and ferritin, for assessing COVID-19 severity. Hence, the difference in the plasma levels of D-dimer can be used to detect underlying comorbidities and co-infections in patients with COVID-19 [15,41,42]. This will help to facilitate clinical management that is both more personalized and more efficient, allowing speedier recovery and significantly reducing the mortality rate.…”
Section: Introductionmentioning
confidence: 99%